Printing of UV-curable transparent conductive polymer composite - ARMAN KANDIRMAZ, EMİNE (TAYLOR & FRANCIS INC, 2020)
The aim of the study is to produce an UV-curable transparent conductive film. First of all, ZnO microparticles were synthesized and modified with acrylate. Then, UV-curable coating formulations having acrylate-modified ZnO microparticles were prepared. Composite polymeric matrix has been printed on the glass surface with screen printing. Attenuated Total Reflectance Fourier Transform Infrared Spectroscopy, current?voltage meter, goniometer, SEM and thermogravimetric analysis were used for chemical structure, electrical surface and thermal properties. As a result; all materials were successfully produced and dispersed onto the surface homogenously. It has been observed that ZnO added screen-printed lines increased the conductivity. UV-curable coating formulations containing ZnO were effectively applied by screen printing.
Keywords: ZnO; microparticle; composite; acrylate modified; conductivity; ZNO; FILMS